Experimental transmission of Zika virus by mosquitoes from central Europe - Heitmann, Anna (Euro Surveill, 2017)
Mosquitoes collected in Germany in 2016, including Culex pipiens pipiens biotype pipiens, Culex torrentium and Aedes albopictus, as well as Culex pipiens pipiens biotype molestus (in colony since 2011) were experimentally infected with Zika virus (ZIKV) at 18 °C or 27 °C. None of the Culex taxa showed vector competence for ZIKV. In contrast, Aedes albopictus were susceptible for ZIKV but only at 27 °C, with transmission rates similar to an Aedes aegypti laboratory colony tested in parallel.